The March of Islam: TimeFrame AD 600 - 800 (Alexandria, Virginia, 1988)
This book describes the historical events and the various civilizations that flourished throughout the world, with emphasis on the March of Islam, from AD 600 to 800.
Keywords: middle ages - history